Global correlation of lower mantle structure and past subduction. Issue 10 (23rd May 2016) - Domeier, Mathew; Doubrovine, Pavel V.; Torsvik, Trond H.; Spakman, Wim; Bull, Abigail L.
Abstract: Advances in global seismic tomography have increasingly motivated identification of subducted lithosphere in Earth's deep mantle, creating novel opportunities to link plate tectonics and mantle evolution. Chief among those is the quest for a robust subduction reference frame, wherein the mantle assemblage of subducted lithosphere is used to reconstruct past surface tectonics in an absolute framework anchored in the deep Earth. However, the associations heretofore drawn between lower mantle structure and past subduction have been qualitative and conflicting, so the very assumption of a correlation has yet to be quantitatively corroborated. Here we show that a significant, time‐depth progressive correlation can be drawn between reconstructed subduction zones of the last 130 Myr and positive S wave velocity anomalies at 600–2300 km depth, but that further correlation between greater times and depths is not presently demonstrable. This correlation suggests that lower mantle slab sinking rates average between 1.1 and 1.9 cm yr −1 . Key Points: Significant correlation between reconstructed subduction of the last 130 Myr and mantle structure at 600 to 2300 km depth Further correlation (beyond 2300 km/130 Ma) not presently demonstrable due to uncertainties in tomographic and paleogeographic models Subducted slabs sink through the lower mantle, on average, at rates between 1.1 and 1.9 cm yr −1